Analysis of Sedimentation for The Optimization of Lempake Dam Operations for Flood Control for The City of Samarinda, Province of East Kalimantan - Erryanto, Sandi; Andawayanti, Ussy; Suhartanto, Ery (Civil and Environmental Science Journal (CIVENSE), 2021)
The Lempake Dam currently functions as a dam that provides raw water for irrigation and clean water, besides its indirect functioning as the only flood control dam in the Karangmumus sub-watershed. Current conditions indicate that the Lempake Reservoir has experienced decreased capacity from year to year. At the normal water level, the reservoir capacity of Lempake Reservoir in 2013 was 0.76 million m3 and in 2018 was 0.39 million m3. Therefore, efforts are needed to control reservoir sedimentation and reservoir operations to allow the Lempake Dam to continue to function as a flood control reservoir. This study was carried out by analyzing the volume of sedimentation in the reservoir using the ArcGIS program and analyzing the flood hydrograph at the site by flood routing at the Pasar Segiri River, optimizing reservoir operations, and mapping flood inundation using the RAS Mapping program (HEC-RAS). The results showed that the storage volume in 2020 is predicted to be 0.241 million m3 with an annual sediment rate of 0.074 million m3. From the flood routing analysis and optimization of reservoir operations, the cross-sectional capacity of the river in Pasar Segiri (safe limit elevation +3.30 m) is insufficient for a flood discharge of a return period of more than 2 years (more than 222.14 m3/sec) for Scenario 1, and of more than 5 years (more than 320.48 m3/sec) for Scenario 2.